Arctic dimension of global warming - G. V. Alekseev (Лëд и снег, 2015)
A brief assessment of the global warming in the Arctic climate system with the emphasis on sea ice is presented. The Arctic region is coupled to the global climate system by the atmosphere and ocean circulation that providesa major contribution to the Arctic energy budget. On this basis using of special indices it is shown that amplification of warming in the Arctic is associated with the increasing of meridional heat transport from the low latitudes.